Costs and benefits of financial globalization in Caribbean subregion (2002)
Examines the main trends in capital flows in the Caribbean, with a view to determining the costs and benefits of the impact of globalization on capital flows in the subregion.
Keywords: CAPITAL MOVEMENTS